2007
DOI: 10.1194/jlr.m700067-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different doses of atorvastatin on human apolipoprotein B-100, B-48, and A-I metabolism

Abstract: Nine hypercholesterolemic and hypertriglyceridemic subjects were enrolled in a randomized, placebocontrolled, double-blind, crossover study to test the effect of atorvastatin 20 mg/day and 80 mg/day on the kinetics of apolipoprotein B-100 (apoB-100) in triglyceride-rich lipoprotein (TRL), intermediate density lipoprotein (IDL), and LDL, of apoB-48 in TRL, and of apoA-I in HDL. Compared with placebo, atorvastatin 20 mg/day was associated with significant reductions in TRL, IDL, and LDL apoB-100 pool size as a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 47 publications
(51 reference statements)
7
68
0
Order By: Relevance
“…Moreover, atorvastatin therapy in hyperlipidemic men has been shown to stimulate intestinal mRNA expression of the LDL receptor and Niemann-Pick C1Like 1 and to decrease mRNA levels dysbetalipoproteinemia ( 38,39 ), and CHD ( 40,41 ). The reductions have been associated with enhanced clearance of apoB-48 ( 22 ) and chylomicron-like emulsions ( 42 ) in subjects with dyslipidemia. In subjects with diabetes, Hogue et al (43) found that atorvastatin reduced TRL apoB-48 concentrations primarily by decreasing its production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, atorvastatin therapy in hyperlipidemic men has been shown to stimulate intestinal mRNA expression of the LDL receptor and Niemann-Pick C1Like 1 and to decrease mRNA levels dysbetalipoproteinemia ( 38,39 ), and CHD ( 40,41 ). The reductions have been associated with enhanced clearance of apoB-48 ( 22 ) and chylomicron-like emulsions ( 42 ) in subjects with dyslipidemia. In subjects with diabetes, Hogue et al (43) found that atorvastatin reduced TRL apoB-48 concentrations primarily by decreasing its production.…”
Section: Discussionmentioning
confidence: 99%
“…Relative to placebo, torcetrapib decreased plasma TG levels by 21 ± 8% ( P = 0.04) in the once daily cohort, by 7 ± 8% ( P not signifi cant) in the The SAAM II program (University of Washington, Seattle, WA) was used to determine the fractional catabolic rate (FCR) of apoB-48 using a previously described multicompartmental model ( 22,24 ). The model assumed a constant enrichment of the precursor pool, as has been demonstrated in metabolic studies using a primed-constant infusion to administer labeled leucine ( 22,24,25 ). Determination of the FCR is independent of the level of precursor enrichment.…”
Section: Effects Of Torcetrapib On Nonfasting Concentrations Of Apob-mentioning
confidence: 99%
See 1 more Smart Citation
“…Large ␣-1 particles increase with weight loss, niacin, certain statins (atorvastatin, rosuvastatin), and CETP inhibitors (52)(53)(54)(55)(56)(57). Increasing the concentrations of apo AI in ␣-1 HDL to Ͼ200 mg/L (0.52 mmol/L) with a simvastatin/niacin combination has been associated with lack of progression and in some individuals with regression of coronary atherosclerosis (51 ).…”
Section: -D Gel Electrophoresismentioning
confidence: 99%
“…6 However, most cases of hypercholesterolemia seen in the general population are likely due to reduced LDL uptake from plasma either resulting from reduced LDLR activity or to 34 Effective pharmacologic treatment with statins results in enhanced LDL clearance from plasma. 35 The next section will describe the molecular mechanisms responsible for these changes that lead to lower LDL levels ( Figure 3). …”
Section: General Overviewmentioning
confidence: 99%